LANDASAN DAN FUNGSI PENDIDIKAN DAN PEMBELAJARAN - Khairunnisa; Habib Anwar Al Anshori (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education and learning are two main components that cannot be separated in the process of human development. Education serves as a means of character formation, potential development, and the inheritance of cultural and moral values ​​in social life. Meanwhile, learning is a core process in the delivery of knowledge, skills, and attitudes that is carried out in a planned and systematic manner. This article aims to analyze the foundations and functions of education and learning in the context of holistic student development. The research uses a qualitative approach with a literature study method through the analysis of various scientific sources, books, journals, and educational documents. The results of the study indicate that education has several main foundations, namely philosophical, psychological, sociological, religious, technological, cultural, historical, and juridical foundations that form the basis for the implementation of education. The functions of education include the development of human potential, personality formation, cultural preservation, social control, and the preparation of a quality workforce. In the learning process, teachers act as facilitators who create an active, creative, and innovative learning environment so that educational goals can be optimally achieved. In addition, learning also serves to improve critical thinking skills, social skills, and student independence. Thus, the foundation and function of education and learning have an important role in creating a generation that is knowledgeable, has character, and is able to face the challenges of modern development.